Reinventing the Social Scientist and Humanist in the Era of Big Data A Perspective from South African Scholars - Brokensha, Susan; Kotzé, Eduan; Senekal, Burgert A. (UJ Press, 2019)
This book explores the big data evolution by interrogating the notion that big data is a disruptive innovation that appears to be challenging existing epistemologies in the humanities and social sciences. Exploring various (controversial) facets of big data such as ethics, data power, and data justice, the book attempts to clarify the trajectory of the epistemology of (big) data-driven science in the humanities and social sciences.